PRODUCTIVITY OF SPRING CROPS AT A MINIMUM PRIMARY TILLAGE IN THE CONDITIONS OF SARATOV PRAVOBEREZHIE (RIGHTBANK) - A. P. Solodovnikov; E. D. Denisov; F. P. Chetverikov; A. D. Yanikov (Зерновое хозяйство России, 2018)
The article gives the results of the study of different methods of tillage (traditional, minimum and zero tillage) on productivity of spring wheat, spring barley, oats and lentil.In dry time at a primary stage of using the technologies of saving agriculture productivity of spring crops was the most after plowing. In the years of sufficient moisture there were no differences among primary tillage.  The researches showed that cultivation of early spring crops in the conditions of Saratov Pravoberezhie decreased their productivity if energy-saving technologies of primary tillage were used. In average, during 5 years traditional tillage provided the largest productivity of spring wheat (1,15 t/ha), spring barley (1,42 t/ha), oats (1,70 t/ha) and lentil (1,12 t/ha), that exceeded the productivity of the crops on 18,3, 16,9, 8,8, 8,9% at a minimum tillage and on 16,5, 19,7, 16,5, 26,8% at zero tillage. Spring barley, spring wheat and lentil are the most demanding to tillage crops with variation coefficients 9,3%; 10,0%; 12,5% respectively. Oats responded to intensity and depth of tillage weaker with a variation coefficient 6,4%.  Statistics of the field data showed that lentil (with a variation coefficient 36,6-44,8%) and oats (with a variation coefficient 37,1-47,2%)  were the most stable to clime crops with constant productivity  in the rightbank areas of the Saratov region. Spring wheat (with a variation coefficient 49,1-53,2%) and spring barley (with a variation coefficient 73,3-87,6%) showed less stable productivity under the same conditions.